Prospective Teachers’ Intercultural Sensitivity as the Effort to Actualize the Multicultural Education - Muhamad Uyun (AL-ISHLAH: Jurnal Pendidikan, 2022)
In response to the cultural diversity in Indonesia, multicultural education is required to provide the students with a proper level of intercultural sensitivity. However, to prepare for an ideal multicultural education for future generations, teachers must undoubtedly master intercultural sensitivity, even since they are still studying in university, as prospective teachers. Therefore, this study aimed to quantitatively investigate the intercultural sensitivity of prospective teachers at UIN Raden Fatah Palembang and IAIN Curup. As a result, the portrait of prospective teachers’ intercultural sensitivity could be used as references in developing their characters as prospective multicultural educators. The respondents of this study were 1,000 prospective teachers at UIN Raden Fatah Palembang and 800 prospective teachers at IAIN Curup. The data were garnered using a structured questionnaire to obtain accurate percentages of the intercultural sensitivity level of prospective teachers. The data were then analyzed using descriptive statistics. The findings revealed that prospective teachers at the two universities had a high level of intercultural sensitivity. The research’s limitations, implications, and recommendations are provided following the data discussion and conclusion. AbstrakMenanggapi keberagaman budaya di Indonesia, pendidikan multikultural diperlukan untuk syarat dalam mempersiapkan siswa dengan kepekaan antarbudaya yang tepat. Dalam hal ini pendidik harus mempersiapkan pendidikan multikultural yang ideal bagi generasi mendatang, guru tentunya harus menguasai kepekaan antarbudaya, bahkan sejak mereka masih kuliah, sebagai calon guru. Oleh karena itu, penelitian ini bertujuan untuk mengetahui secara kuantitatif tentang kepekaan antarbudaya terhadap calon guru di UIN Raden Fatah Palembang dan IAIN Curup. Hasilnya, potret kepekaan antarbudaya calon guru bisa dijadikan acuan untuk mengembangkan karakter mereka sebagai calon pendidik multikultural. Partisipan dalam penelitian ini adalah 1000 calon guru di UIN Raden Fatah Palembang dan 800 calon guru di IAIN Curup. Data dikumpulkan mengunakan kuisioner yang terstruktur guna untuk mendapatkan hasil yang akurat dari tingkat sensitivitas antarbudaya calon guru. Data tersebut kemudian di analisis dengan mengunakan statistik deskriptif.Temuan mengungkapkan bahwa calon guru di kedua universitas mempunyai tingkat tinggi terhadap sensitivitas antarbudaya. Keterbatasan, implikasi dan rekomendasi penelitian disajikan setelah pembahasan dan kesimpulan data.